Rethinking the Paradigm of High-Performance Design: New Borders Between Vernacular and Contemporary Approaches - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2021)
Vernacular architecture, as a gain of understanding the human needs within the social and cultural heritage and the environmental context, presents instructive examples of design solutions for the built environment. However, this phenomenon has been replaced by contemporary architecture practices over time. On the other hand, due to the global warming, depletion of sources and many more the paradigm of high-performance design recently address energy efficiency, thermal and visual comfort and usage of local resources, has already originated in the vernacular architecture and has been slightly or fairly dismissed from the contemporary architecture practices. Thus, the target of achieving a high performance built environment in contemporary architecture has started setting new borders where it could interact with vernacular approaches. This chapter aims to present the evolution of borders from vernacular to contemporary architecture or vice versa. Therefore, vernacular approaches are represented through a design hierarchy and discussed as a consequence of setting new borders through rethinking the paradigm of high-performance design. Finally, a literature review, using bibliometrics, is carried out to verify the hypothesis of the paradigm shift and to put forth a future projection for the high-performance paradigm. © 2021, Springer Nature Switzerland AG.
Keywords: Bibliometric analysis; Contemporary; High-performance; Neighbourhood; Vernacular